The National Association for Music Therapy: a history from 1981 to 1985 - Bartoldus, Santana M. H., author; Davis, William B., advisor; LaGasse, A. Blythe, committee member; Cleary, Anne, committee member (Colorado State University. Libraries, 2016)
Beginning in 1950, the National Association for Music Therapy (NAMT) served as the primary professional association for music therapists in the United States until the founding of the American Association for Music Therapy (AAMT; originally known as the Urban Federation of Music Therapists) in 1971 and subsequent reunification of these associations into the American Music Therapy Association (AMTA) in 1998. This study examines in detail the activities of NAMT from 1981 to 1985. During this time period, NAMT grew in membership, increased in stability, and contributed to many advances in the study and practice of music therapy. Important contributions to the field are identified and discussed, as are the individuals and groups whose efforts made these advances possible. The Association’s relocation of its national office, the first printing of Music Therapy Perspectives, the founding of the Certification Board for Music Therapists, and the first administration of the music therapy Board Certification exam are explored in detail as NAMT’s most lasting accomplishments during the early 1980s.